The effect of physical activities on internet addiction in college students: the mediating effect of self-control - Sun, Yan; Wang, Yu; Yu, Hongjun; Liu, Jingmin; Feng, Xiaolu (Frontiers in Psychology, 2025)
ObjectiveTo investigate the relationship between college students' physical activities and Internet addiction, to investigate the role self-control control plays in this relationship, and to provide a theoretical foundation for the alleviation of college students' tendency to Internet addiction and intervention treatment.MethodsA questionnaire survey was conducted on 471 college students using the International Physical Activity Questionnaire (IPAQ), the Revised Chen Internet Addiction Scale (CIAS-R), and the Self-Control Scale (SCS).ResultsInternet addiction was significantly negatively correlated with physical activities (overall; min/WK, r = −0.115, P < 0.05), with high-intensity physical activities (min/WK, r = −0.179, P < 0.01), and with low-intensity physical activities (r = −0.103, P < 0.05); self-control was significantly positively correlated with physical activities (overall; min/WK, r = 0.150, P < 0.01), with moderate—intensity physical activities (min/WK, r = 0.139, P < 0.01) while it was significantly negatively correlated with Internet addiction (min/WK, r = −0.349, P < 0.01). The mediating effect follows the path: physical activity → self-control → internet addiction.ConclusionPhysical activity can have a direct negative effect on college students' Internet addiction, and also influence Internet addiction through the mediating effect of self-control.